Microparticulate and nanoparticulate drug delivery systems for metformin hydrochloride. (12th October 2016) - Cetin, Meltem; Sahin, Selma
Abstract: Context : Metformin hydrochloride is a biguanide derivative widely used for the treatment of type 2 diabetes, prescribed nearly to 120 million people worldwide. Metformin has a relatively low oral bioavailability (about 50–60%). Although the major effect of metformin is to decrease hepatic glucose output as an antihyperglycemic agent, its inhibitory effects on the proliferation of some cancer cells (e.g. prostate, breast, glioma cells) have been demonstrated in the cell culture studies. Development of novel formulation (e.g. microparticles, nanoparticles) strategies for metformin might be useful to improve its bioavailability, to reduce the dosing frequency, to decrease gastrointestinal side effects and toxicity and to be helpful for effective use of metformin in cancer treatment. Objective : The main aim of this review is to summarize metformin HCl-loaded micro- and nanoparticulate drug delivery systems. Method : The literature was rewieved with regard to the physicochemical, pharmacological properties of metformin, and also its mechanism of action in type 2 diabetes and cancer. In addition, micro- and nanoparticulate drug delivery systems developed for metformin were gathered from the literature and the results were discussed. Conclusion : Metformin is an oral antihyperglycemic agent and also has potential antitumorigenic effects. The repeated applications of high doses of metformin (as immediate release formulations) are needed for an effective treatment due to its low oral bioavailability and short biological half-life. Drug delivery systems are very useful systems to overcome the difficulties associated with conventional dosage forms of metformin and also for its effective use in cancer treatment.